Cauchy’s problem and measure of noncompactness - BELOUADAH, Assia; Encadreur: GAGUI, Bachir (University of M'sila, 2023)
In This Work, we study the notion the measure of noncompactness and we applied to the fractional differential equations on the goal to proof the existence of solution using fixed point theory combined with the Kuratouskii measure of noncompactness
Keywords: Measure of noncompactness of Kuratouskii, Fixed point theorem, fractional differential equations, derivative Caputo.